PEMANFAATAN MEDIA SOSIAL FACEBOOK SEBAGAI MEDIA INFORMASI PEMERINTAH BAGI MASYARAKAT DESA TASOKKO KABUPATEN MAMUJU TENGAH SULAWESI BARAT - Mahyana, Nicky; Unde, Andi Alimuddin; Fatimah, Jeanny Maria (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
Social media has become an effective communication tool for disseminating information, including in village government. The purpose of this study was to analyze the use of Facebook as an information medium for the community of Tasokko Village, Central Mamuju Regency, West Sulawesi. The approach used was descriptive qualitative with interviews, observation, and documentation techniques. The results showed that Facebook increases information transparency, accelerates news dissemination, and facilitates community access to village information. However, obstacles emerged such as limited internet access, dependence on quotas, the use of personal accounts for official information, and a lack of regular updates. The study concluded that Facebook has great potential as an effective communication medium for village government, but requires optimization. Recommendations include increasing digital literacy, using structured official accounts, and improving digital infrastructure to ensure equitable access to information for the wider and more inclusive community. This study contributes to understanding the role of Facebook as a communication tool in villages and provides insights for policymakers to increase the efficiency of information delivery and improve existing digital access. Keywords: Social Media; Facebook; Information; Government Transparency